-1.4v+2.3=-5.4v-5.7

Simple and best practice solution for -1.4v+2.3=-5.4v-5.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1.4v+2.3=-5.4v-5.7 equation:


Simplifying
-1.4v + 2.3 = -5.4v + -5.7

Reorder the terms:
2.3 + -1.4v = -5.4v + -5.7

Reorder the terms:
2.3 + -1.4v = -5.7 + -5.4v

Solving
2.3 + -1.4v = -5.7 + -5.4v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '5.4v' to each side of the equation.
2.3 + -1.4v + 5.4v = -5.7 + -5.4v + 5.4v

Combine like terms: -1.4v + 5.4v = 4v
2.3 + 4v = -5.7 + -5.4v + 5.4v

Combine like terms: -5.4v + 5.4v = 0.0
2.3 + 4v = -5.7 + 0.0
2.3 + 4v = -5.7

Add '-2.3' to each side of the equation.
2.3 + -2.3 + 4v = -5.7 + -2.3

Combine like terms: 2.3 + -2.3 = 0.0
0.0 + 4v = -5.7 + -2.3
4v = -5.7 + -2.3

Combine like terms: -5.7 + -2.3 = -8
4v = -8

Divide each side by '4'.
v = -2

Simplifying
v = -2

See similar equations:

| 3(4m+m)=-75 | | 4y+6=-18 | | 3y=32 | | 5x-5/-10=70 | | 12(w+3w)=144 | | -u-19=-5u+13 | | x^6-14x^3=0 | | 18(x+2)+2x=17x+36 | | -2/5=-?m+3/5 | | (4-7j)(3-4j)= | | 6=-4(n-1) | | -2y+3=-4y-5 | | -5x+6y=120 | | -0.7x+2.69=-0.5x+3.49 | | 4x-3=x-2 | | 2x-8x+10/2x | | 20y^4-125y^2=0 | | -x^2+6x+1=0 | | (6+j)-(3-4j)= | | 5q/10d+15q | | 2x-y=-20 | | 4.4x-23=2.4x+7 | | 2n+3/8n^2+4+n-3/8n^2+4n | | 20-4x=25-5x | | h-=? | | 0.2x+0.7=-0.9 | | 3(x-9.2)=3.6 | | y=-(x+4) | | -6y=3.84 | | 45-2m=15+3m | | 4(4x+3)=7(x-2)+10 | | f(x)=2(22)-5 |

Equations solver categories